Legislative Response to College Students’ Non-altruistic Charitable Donations (Asian Journal of Social Science Studies, 2022)
Donation behavior is premised on the willingness to donate, and the latter is based on the motivation of donation. Only by fully recognizing the donors’ donation motivation can their willingness to donate be better stimulated, thereby guiding and encouraging more donation behaviors. By conducting a questionnaire survey of charitable donations in colleges and universities, it is found that non-altruistic motivations including material interests and specific preferences are positively correlated with human well-being & happiness, while motivations such as honor pursuits & social identity have a negative correlation with human well-being & happiness. Therefore, we should actively build an incentive mechanism for college students’ charitable activities in response to their pursuits of material interests, and strive to improve the incentive mechanism to stimulate college students’ personalized donation willingness and suit their specific preferences. At the same time, we should try to set up a restriction mechanism for college students’ non-altruistic charitable donation motivations, and guard against the reversing guiding effect of motivation of honor pursuits & social identity on college students’ charitable donations behavior.